Comparison of fasting lipid profile in ischemic and haemorrhagic stroke patients of a tertiary care hospital - Gnanamoorthy, Kothai; Suthakaran, Prasanna Karthik; Rajendran, Kannan; Deepak, Keerthi (International Journal of Advances in Medicine, 2016)
Background: Stroke is one of the leading causes of death and disability in India. Dyslipidaemia as a risk factor for cerebrovascular accidents have been explored in various studies and have been definitely established with the findings of many landmark trials. The relation of circulating cholesterol to ischemic stroke does not resemble its well-known relation to coronary heart disease and hence needs to be explored in detail. Methods: 72 patients with a first ever diagnosis of cerebrovascular disease whose onset was within the preceding three days were enrolled in the study. Lipid profile abnormalities were documented in these patients and they were followed up for 30 days. Results: The mean age was 60.7 ± 11.0 years in the ischemic group and 52.3±10.2 years in the haemorrhagic group (P=0.004). The mean total cholesterol (TC) levels and the mean LDL – cholesterol (LDL – C) levels were higher in the ischemic stroke patients and these differences were statistically very significant. (183.7± 34.5 versus 148.5±30.6, P = 0.0002, 118.7±26.7 versus 81.4±22.0, P = 0.0001) The differences in the mean triglycerides (TG), mean HDL – cholesterol (HDL – C) and mean VLDL – cholesterol (VLDL – C) levels were not statistically significant between the two groups. Conclusions: In this study, the mean TC and LDL – C levels were significantly much higher in the ischemic stroke patients when compared to patients with haemorrhagic stroke. The findings from this small study suggest that there may be a limit to the lowering of LDL – Cholesterol levels. Some studies have shown that lower levels are associated with increased risk of haemorrhagic stroke rather than ischemic stroke, though conclusive evidence is still lacking.